A Study of Thematic Learning in Discipline Character Cases - Nursakinah Nursakinah; Jauhar Jauhar (Journal of Basic Education Research, 2023)
This study aims to describe thematic learning that has a correlation in helping the formation of disciplinary character in students. The method used in this research is a qualitative method to get a deeper understanding of a problem. . The subjects of this study were students in class III of State Elementary School 166/1 Olak Rambahan, totaling 11 students who were obtained using random sampling technique. Instruments of data collection were carried out through observation (observation of educators and students) and conducting interviews with students. Data analysis used interviews and observations. Based on the results of the research that has been done, it can be concluded that the thematic learning applied to class III Elementary School will have a tremendous impact on educators, students and the school environment.